Smart optimized Reconfigurable Trans-Receiver System - Prasun Chakrabarti, Vivek Jain (International Journal of Advanced Science and Technology, 2020)
To establish communication between earth station and space craft real time high speed transmission is required with low power consumption for increase the life of battery space craft. To achieve these advanced design goals by Reconfigurable trans-receiver. The power of that system is optimized by applying placement and routing algorithm such as global routing and river routing. After that we are applying artificial intelligence on that system for selection of width of the data width of communication on the basis of data rate. The data width of Trans-Receiver is reconfigurable from 8 bit to 512 bit.